PENGARUH REBUSAN KAYU MANIS TERHADAP KADAR GULA DARAH PASIEN DIABETES MELLITUS TIPE II - Awaluddin Awaluddin; Anita Syarifah; Aslina Aslina (Ensiklopedia of Journal, 2021)
Indonesia is in the 7th rank among the top 10 countries suffering from diabetes mellitus with 10.7 million sufferers.Blood sugar levels in diabetes mellitus patients can be lowered by consuming Cinnamon. Cinnamon contains essential oils, such as eugenol and polyphenols that help increase insulin receptor proteins in cells. The purpose of this study was to measure the effectiveness of cinnamon decoction on blood sugar levels in patients with type II diabetes mellitus. This research design is a quasi-experimental. The research was conducted in the working area of Pematang Pudu Public Health Center, Mandau District, with 10 respondents. Data analysis used paired t test. The results showed that there was a significant difference between blood sugar levels before and after in the experimental group with p-value = 0.000 (p